The Predictive Value of Genetic Analyses in the Diagnosis of Tetrahydrobiopterin (BH4)-Responsiveness in Chinese Phenylalanine Hydroxylase Deficiency Patients - Zhu, Tianwen (Sci Rep, 2017)
Molecular characterization of PAH deficiency has been proven essential in establishing treatment options. We examine the diagnostic accuracy of two genetic assays to predict BH4 responsiveness: to determine whether the AV sum test or mutation-status assessment test can obviate the need for BH4 loading in Chinese patients. The overall predicted response in 346 patients was 31.65% by the AV sum test and 25.43% by the other assay; both percentages were lower than 51.06% derived from loading results in 94 patients. Responders were compound heterozygotes with definite BH4 responsive mutations, while non-responders had null/null ones; some consistently with specific mutations and genotypes. The sensitivity and specificity of the assays were 81.1% and 92.5% for the AV sum, and 82.9%, 97.3% for the other. An AV sum cutoff >2 has a positive predictive value (PPV) of 90.9%, while the presence of at least one BH4 responsive mutation has a PPV of 97.1%. The two approaches showed good concordance. Our data confirmed that the mutation-status assessment has a higher diagnostic accuracy in predicting response for Chinese patients than the AV sum test. BH4-responsiveness may be predicted or excluded from patients’ molecular characteristics to some extent, thus some patients may avoid the initial loading.